Pengaruh Stres Fisik terhadap Kadar Kreatinin Serum Tikus Wistar Jantan (Rattus norvegicus) (The Effect of Physical Stress on Serum Creatinine of Male Rattus norvegicus) - Putu Ratih Pradnyani Dewi; Hairrudin Hairrudin; Rena Normasari (Pustaka Kesehatan, 2016)
Physical stress is a condition that caused by severe physical activities which can increase free radicals production causing oxidative stress. Oxidative stress causing the organs failure include the kidney. It damage glomerulus causing decrease in GFR and tubular cell damage causing cumulation of creatinine and raise creatinine serum. This study investigated the difference of serum creatinine of male Rattus norvegicus with physical stress and without physical stress. Ten male Rattus norvegicus aged 2-3 months were divided into two groups : control and treatment group. Control group without physical stress but treatment group was given physical stress 30 minutes of swimming stress in the morning everyday for 10 days. The creatinine serum measured by Jaffe reaction. The normal range of serum creatinine for Rattus norvegicus was 0,578-1,128 mg/dl. The result of serum creatinine for control group was 0,52 mg/dl and treatment group was 0,62 mg/dl,both still in normal range. The analysis using Mann Whitney showed the significance of 0,23 (p>0,05). We can conclude that there was no difference of serum creatinine of male Rattus norvegicus with physical stress and without physical stress. Keywords: physical stress, oxidative stress, serum creatinine